Thermodynamic and kinetic studies on interaction of some transition metal ions with tryptophan - Ghiamati, Ebrahim; Abazari, Zahra (European Journal of Chemistry, 2017)
Amino acid of tryptophan (Trp) was chosen as a drug. A systematic approach was made to study its interaction with some transition metal ions, and qualitatively and quantitatively examine the thermodynamic and kinetic phenomena on this model drug. To accomplish these tasks, the stability constants of Trp complexes with Fe(III), Co(II), Ni(II), Cu(II), Zn(II) and Pb(II) at temperatures of 25, 30, 35, and 40 °C were determined potentiometrically, utilizing modified Bjerrum’s method. Potentiometric titrations were carried out in water, and water:dioxane mixture (50:50, v:v). Our findings showed that the stability constants of the complexes increased as the dioxane content was raised or temperature was elevated. The negative values of ΔG° are indication of spontaneity of the processes. ΔH° values are positive, conveying the complex formation is an endothermic process and ΔS° values are positive contributing more to spontaneity, causing reaction favoring and disordering. The variations of natural logarithm of the stability constants versus 1/T are linear leading to evaluation of the stability constant of the complexes at any temperature. Moreover, kinetic study gave rise to estimation of rate constant and activation energy for each complex formation process. It was concluded that the order of increasing stability of the complexes is: kf Co(II)-Trp » kf Zn(II)-Trp < kf Pb(II)-Trp < kf Ni(II)-Trp < kf Cu(II)-Trp < kf Fe (III)- Trp. Furthermore the activation energy values for the aforementioned complexes in water-dioxane mixture obeyed the following trend Ea Zn(II)-trp < Ea Fe(III)-Trp < Ea Ni(II)-trp < Ea Co(II)-trp <Ea Cu(II)-trp <Ea Pb(II)-trp.